2020
DOI: 10.3233/jpd-202029
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Lexicon of Fatigue in Parkinson’s Disease

Abstract: Background: Fatigue in Parkinson's disease (PD) is multifaceted and associated with reduced quality of life. In turn, the language used by people with PD to describe fatigue is variable and poorly understood. We sought to elucidate the lexicon of fatigue using a qualitative grounded theory approach. Objective: The objective of this study was to understand how patients with PD describe fatigue. Methods: A pre-study phase of online journaling (Phase 1) provided information regarding topics of importance to patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…This intriguing difference between our results and the results of other studies 25,27 that recruited smaller proportions of women warrants further study. In addition, our own prior work analyzing free-text responses from the same cohort 5 found that women were more likely to describe fatigue as overwhelming than men. These apparent contradictions may reflect aspects of fatigue and/or quality of life that are differently captured in quantitative scales such as the PFS-16 or PDQ-8 compared with free-text responses.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This intriguing difference between our results and the results of other studies 25,27 that recruited smaller proportions of women warrants further study. In addition, our own prior work analyzing free-text responses from the same cohort 5 found that women were more likely to describe fatigue as overwhelming than men. These apparent contradictions may reflect aspects of fatigue and/or quality of life that are differently captured in quantitative scales such as the PFS-16 or PDQ-8 compared with free-text responses.…”
Section: Discussionmentioning
confidence: 95%
“…Participants in the PD cohort of the Fox Insight study were invited to participate in this substudy on fatigue in PD 5 if they met the following criteria: provided data on their age, sex, year of diagnosis, and completed the Fox Insight assessments regarding depression (15‐item Geriatric Depression Scale [GDS‐15]) and Physical Activity Scale for the Elderly (PASE) within the prior 90 days. This latter requirement was necessitated by other study objectives not considered here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a starting point, clear definitions and strict separation from HRQoL is required. In terms of the difficulty of mapping qualitative characteristics, one may advocate for qualitative assessment methods, e.g., in the form of structured interviews with open questions as a possible remedy [ 37 ]. These techniques may be particularly helpful to define additional dimensions to those implied in HRQoL questionnaires.…”
Section: Moving Towards a Holistic Measurement Of Quality Of Life In ...mentioning
confidence: 99%
“…This work occurred as part of the Michael J Fox Foundation's Parkinson's Disease Education Consortium (PDEC) 2018 research program on the experience and impact of fatigue in PD, as described previously in detail [35]. Briefly, the sample was drawn from the Fox Insight (FI) cohort.…”
Section: Samplementioning
confidence: 99%